2023
DOI: 10.4293/jsls.2022.00088
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Living Donor Nephrectomy: A Single Center Comparison of Three Different Techniques

Abstract: Background and Objectives: In this study, we compare three different surgical approaches at a single institution. Pure laparoscopic donor nephrectomy with Pfannenstiel incision (PLDN) was compared with hand-assisted laparoscopic donor nephrectomy via midline hand port (HALDNM) and hand-assisted laparoscopic donor nephrectomy via left iliac hand port (HALDNL).Methods: This study included all laparoscopic left donor nephrectomies performed at our institution between January 1, 2020 and December 31, 2021. Donor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…18 Hartmann et al reported 1,800 cases of living donors, of which only seven developed end-stage renal disease. 19 Another study reported 402 cases of living donors in Sweden, and only one required hemodialysis due to postoperative renal failure. 20 In our study, the donors did not develop end-stage renal disease in the long-term follow-up, a result consistent with the findings of previous studies.…”
Section: Donormentioning
confidence: 99%
“…18 Hartmann et al reported 1,800 cases of living donors, of which only seven developed end-stage renal disease. 19 Another study reported 402 cases of living donors in Sweden, and only one required hemodialysis due to postoperative renal failure. 20 In our study, the donors did not develop end-stage renal disease in the long-term follow-up, a result consistent with the findings of previous studies.…”
Section: Donormentioning
confidence: 99%